Records of the Council of Australian State Libraries - Council of Australian State Libraries; National and State Libraries Australasia (1973)
MS 8062 comprises the State Libraries Council Chairman's correspondence, 1973-1988 and minutes, 1973-1986.
The Acc02.65 instalment includes files covering the period January 1998-December 2001.
The Acc02.161 instalment comprises agenda and meeting papers, 1992-1994.
The Acc22.071 instalment comprises records of the Council of Australian State Libraries (CASL) 1996-2006 and National and State Libraries Australasia (NSLA) 2006-2018. The records relate to the Library's collection priority of collecting archives of organisations with peak body responsibilities. Included are correspondence, project proposals, committee, taskforce and working party papers, agenda and meeting papers.
Manuscript reference no.: MS 8062, MS Acc02.065, MS Acc02.161, MS Acc22.071.
The State Librarians' Council was established in 1973 to lobby the Commonwealth Government for funding. The Council's first meeting, held in March 1973, was attended by the state librarians of New South Wales, Western Australia, South Australia, Tasmania, Queensland and Victoria. In 1990 it changed its name to the State Libraries Council with an expanded membership that included the chief executives of the Northern Territory and Australian Capital Territory Library and Information Services, and the National Library of Australia. The State Libraries Council was the predecessor of the Council of Australian State Libraries (CASL), the peak body for the state, territory and national libraries that supported a wide range of collaborative initiatives between member libraries and other organisations in the public sector.
Keywords: Council of Australian State Libraries -- Archives; Library cooperation -- Australia; Government libraries -- Australia; State libraries -- Australia; Librarians